2017
DOI: 10.15171/apb.2017.042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resveratrol on the Structure and Catalytic Function of Bovine Liver catalase (BLC): Spectroscopic and Theoretical Studies

Abstract: Purpose: The study on the interaction between various compounds and macromolecules such as enzymes has been very important for monitoring the alteration of structural and functional properties of them. Resveratrol (3, 5, 4-trihydroxy-stilbene; RES) is a biologically active phytoallexin found in grapes and other food products. This article shows an interaction of native bovine liver catalase (BLC) with natural antioxidant product, trans resveratrol (tRES) using multispectroscopic methods.Methods: The interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…We established that the curcumin-containing dual-drug loaded nanoparticles (MO-FO-CU-CAT) maintain or increase the CAT activity (Figure 7), unlike other antioxidants, which can inhibit the catalase enzymatic function [56,57]. Molecular dynamic simulations have demonstrated that curcumin can significantly increase the activity of bovine liver catalase (BLC) as it favors the access of the substrate to the active site of the enzyme [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We established that the curcumin-containing dual-drug loaded nanoparticles (MO-FO-CU-CAT) maintain or increase the CAT activity (Figure 7), unlike other antioxidants, which can inhibit the catalase enzymatic function [56,57]. Molecular dynamic simulations have demonstrated that curcumin can significantly increase the activity of bovine liver catalase (BLC) as it favors the access of the substrate to the active site of the enzyme [59].…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that catalase undergoes rapid elimination from the bloodstream and is characterized by poor intracellular delivery. Thus, catalase exhibits a short half-life and poor operational stability and reusability as an enzyme, which limits its potential therapeutic applications [55,56,57,58,59,60]. The unstable biomacromolecule can be immobilized in order to increase its stability and improve its enzymatic performance, solubility and specificity [61,62,63,64,65,66,67].…”
Section: Introductionmentioning
confidence: 99%
“…The inherent fluorescence emission of proteins is caused by three aromatic amino acid residues: tyrosine (Tyr), tryptophan (Trp), and phenylalanine (Phe). The Trp residue dominantly is responsible for observed inherent protein fluorescence, because of the low quantum yield of the Phe and Tyr residues . Trp fluorescence properties that come from the indole group in its structure are the most sensitive to its environment (polarity of its micro‐environment, noncovalent interactions, hydrogen bonding and denaturation) and can change upon interaction with various ligands (drugs or small molecules) and protein folding/unfolding.…”
Section: Resultsmentioning
confidence: 99%
“…These results confirmed the Tb(III)-phen-AgNPs system formation and energy transfer from Tb(III)-phen to AgNPs by the FRET process. 27,28 The Stern-Volmer equation was applied to a fluorescence quenching data analysis: 52,53…”
Section: Investigating the Fluorescence Quenching Of The Tb(iii)-phenmentioning
confidence: 99%